SIMPANAN KARBON SEBAGAI SALAH SATU INDIKATOR KESEHATAN HUTAN PADA HUTAN RAKYAT (Studi Kasus di Hutan Rakyat Kelurahan Pinang Jaya, Kecamatan Kemiling, Kota Bandar Lampung, Provinsi Lampung) - Vita Arianasari; Rahmat Safe'i; Arief Darmawan; Hari Kaskoyo (Jurnal Belantara, 2021)
Global climate change and forest health are currently two things that need to be studied more deeply. Forests store carbon, including in the community forests. A healthy forest can perform its function properly including as a carbon sinker as well as a carbon repository. This study aims to analyze carbon storage as an indicator of forest health in community forests in Pinang Jaya Village. The data were collected by using cluster plots based on the method of Forest Health Monitoring (FHM), totaling 15 units. The measurement method used is destructive and non-destructive. The result showed that the average carbon storage in community forests in Pinang Jaya Village is 54.59 tC/ha. The largest contribution to carbon storage was AGB with a percentage of 95.71%, followed by necromass at 4.23%, and 0.05% litter and understorey. Based on the results of the analysis, carbon storage can perform as an indicator of forest health in the community forests of Pinang Jaya Village with the bad, medium, and good categories. The plot clusters are in the Good category (70.61 tC/ha - 83.66 tC/ha), namely cluster plots 13, Moderate categories (57.55 tC/ha - 70.60 tC/ha), namely cluster plots 4 and 14, and the Bad category (44.49 tC/ha - 57.54 tC/ha), namely cluster plots 1-3, 5-12.15, with the percentage of each category of 7%, 13%, and 80%.